Analisis Faktor-Faktor Yang Dapat Mempengaruhi Keputusan Konsumen Dalam Mengambil Kredit Kpr Pada PT. Bank Tabungan Negara Cabang Jember - Haifa Haifa (RELASI : JURNAL EKONOMI, 2019)
This study aims to determine the effect of consumer decisions in taking mortgages at Bank Tabungan Negara Tbk Jember Branch. This study uses Chi-square analysis to determine the relationship between factors that influence consumer behavior (which consists of (1) requirements, (2) credit interest rates and (3) credit installment subsidies) also uses Coeficient Contingency analysis to know the effect on decisions consumers in taking mortgage loans at PT. Bank Tabungan Negara Tbk Jember Branch the population in this study were consumers who took mortgage loans at PT. State Savings Bank (Persero) Tbk. Jember Branch. The total population is 200 respondents where the sample uses the non probability quota sampling method which is a sampling method in which the subjects to be studied are determined in advance of the amount. The number of samples is 50% of the number of respondents as many as 100 The results of the study show that Based on the results of calculations using Chi-square analysis and Coeficient Contingency analysis, the credit application requirements, credit interest rates and credit disbursement realization factors, there is a significant relationship and influence on customer decisions in taking credit at PT. Bank Tabungan Negara Tbk Jember branch